"I just have to take it" - patient safety in acute care: perspectives and experiences of patients with chronic kidney disease - Lucia New; Donna Goodridge; Joanne Kappel; Gary Groot; Roy Dobson (BMC, 2019)
Abstract Background Frequent hospitalizations and dependency on technology and providers place individuals with chronic kidney disease (CKD) at high risk for multiple safety events. Threats to their safety may be physical, emotional, or psychological. This study sought to explore patient safety from the perspectives and experiences of patients with CKD in acute care settings, and to describe willingness to report incidents utilizing an existing safety reporting system. Methods This study was conducted using a qualitative interpretive descriptive approach. Face to face interviews were conducted with 30 participants at their bedside during their current hospital admission. The majority of the participants were 50 years or older, of which 75% had a confirmed diagnosis of end stage renal disease with the remainder at stages 3 or 4 of CKD. Eighty percent of the participants were either on hemo- or peritoneal dialysis. Results Participants expected to receive safe care, to be taken care of, and to be cared for. Safety threats included: sharing a room with patients who were on precautions; lack of cleanliness; and roommates perceived to be threatening. The concepts of being taken care of and being cared for constituted the safety threats identified within the interpersonal environment. Participants felt taken care of when their physical needs are met and cared for when their psychological and emotional needs are met. There was a general lack of awareness of the presence of a safety reporting system that was to be accessible to patients and families by telephone. There was also an overall unwillingness to report perceived safety incidents, although participants did distinguish between speaking up and reporting. Conclusions A key finding was the unwillingness to report incidents using the safety reporting system. Fear of reprisals was the most significant reporting impediment expressed. Actively inviting patients to speak up may be more effective when combined with a psychologically safe environment in order to encourage the involvement of patients in patient safety. System-wide organizational changes may be necessary to mitigate emotional and physical harm for this client population.